Comparative Analysis of Polyphenols in Lycium barbarum Fruits Using UPLC-IM-QTOF-MS - Yanjun Ju; Yujie Wang; Lei Ma; Lu Kang; Hejiang Liu; Xue Ma; Duoyong Zhao (Molecules, 2023)
Variety, geographical origin, and harvest season are important factors affecting the accumulation of polyphenols in Lycium barbarum. In this study, the effects of these factors on the polyphenolic components of this species were analyzed using ultra-performance liquid chromatography ion mobility quadrupole time-of-flight mass spectrometry. Moreover, the in vitro antioxidant activities of fruit extracts from this species were evaluated. The total polyphenolic contents of L. barbarum fruits from Jinghe County in Xinjiang and Zhongning County in Ningxia were 5.52–11.72 and 7.06–9.37 mg (gallic acid equivalent)/g dry weight, while the total flavonoid contents of L. barbarum fruits from these regions were 12.52–30.29 and 12.67–20.77 mg (rutin equivalent)/g dry weight, respectively. Overall, 39 types of polyphenols were identified in the fruit extracts, including 26 flavonoids, 10 phenolic acids, and three tannins. Of these, 11 polyphenols were quantitatively analyzed, which revealed rutin to be the most dominant polyphenolic component in fruits from Jinghe and Zhongning. There were significant differences (p < 0.05) in the polyphenolic contents and antioxidant activities of L. barbarum fruit extracts, depending on the geographical origin, variety, and harvest season. The antioxidant activity of this species was found to be significantly positively correlated with the polyphenolic contents. This study provided scientific guidance for comprehensive applications of polyphenols from different varieties of L. barbarum from separate geographical origins.